Kombinasi Ekstrak Kulit Buah Nanas dan Mangga yang Memiliki Aktivitas Antioksidan dan Inhibisi Tirosinase - Krismayadi, Krismayadi; Taurhesia, Shelly; Noor, Siti Umrah (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
The peel of pineapple (Ananas comosus (L.) Merr.) and mango (Mangifera indica L.) contain polyphenolics that have antioxidant activity and tyrosinase inhibitor. Both of these activities are useful for skin lightening treatments. The purpose of this study was to determine the value of the antioxidant and tyrosinase inhibitor activity of each pineapple peel extract (EKBN) and mango peel extract (EKBM), and their combination with a ratio of 2:1; 1:1; 1:2. The combination that gives the best value for antioxidant activity and tyrosinase inhibitor may be made for cosmetic preparations. The antioxidant activity of each extract and its combination was determined by the DPPH method, after the antioxidant IC50 value was obtained, then the tyrosinase enzyme inhibitory activity was tested. The results showed that EKBN; EKBM; the combination of EKBN and EKBM with a ratio of 2:1, 1:1, 1:2 has antioxidant activity with IC50 values: 618.42 ppm, 10.29 ppm, 30.73 ppm, 20.20 ppm and 18.04 ppm, has tyroinase inhibitory activity with IC50 of 5,019.98 ppm, 930.85 ppm, 1.992.31 ppm, 2.070.89 ppm and 2.839.75 ppm, respectively. There is a correlation between the IC50 of the combined extract and its weight. the combination of EKBN and EKBM, 1:2 gave the best antioxidant activity results with an IC50 value of 18.04 ppm (very strong) and the combination of EKBN and EKBM, 2:1 gave tyrosinase inhibitory activity with an IC50 value of tyrosinase 1.992.31 ppm. The combination of EKBN and EKBM, 1:2 may be developed further as cosmetic preparations such as serum, liquid spray, and others.